A Novel Control Strategy Based Dynamic Voltage Restorer for Compensation of Voltage Harmonics in Distribution System - Syed Suraya; P. Sujatha P; Bharat Kumar. P (Institute of Advanced Engineering and Science, 2017)
Power quality is one of the areas that the power sector is worried about. Power quality is the measure of practical system resemblance to ideal system. Voltage quality can be defined as the maintenance of voltage waveform shape close to ideal shape with proper magnitude and frequency. Even a slight change in voltage of the system can cause serious damage to the power system. Sensitive loads cannot adjust for small change in voltage. This paper presents Dynamic Voltage Restorer (DVR) for voltage harmonic suppression along with sag/swell compensation in distribution system. DVR is a voltage source converter which sends compensating signals when operated through switches of voltage source converter. This paper presents a novel control strategy to control DVR to block out the voltage harmonics in distribution system. The models and results are developed using MATLAB/SIMULINK software and comparative analysis of source voltage harmonics and load voltage harmonics during sag/swell compensation was tabulated.